2020
DOI: 10.1302/0301-620x.102b3.bjj-2019-0713.r1
|View full text |Cite
|
Sign up to set email alerts
|

The three-year survivorship of robotically assisted versus non-robotically assisted unicompartmental knee arthroplasty

Abstract: Aim There has been a significant reduction in unicompartmental knee arthroplasty (UKA) procedures recorded in Australia. This follows several national joint registry studies documenting high UKA revision rates when compared to total knee arthroplasty (TKA). With the recent introduction of robotically assisted UKA procedures, it is hoped that outcomes improve. This study examines the cumulative revision rate of UKA procedures implanted with a newly introduced robotic system and compares the results to one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 58 publications
0
41
1
Order By: Relevance
“…Several factors such as building additional skin incisions, inserting biocritical registration pins, could increase surgery time to a certain extent. The main concern is that the increased operation time may be a potential risk factor for complications 39 . But there is currently no convincing evidence that the robotic group has higher rate of complications, our research also found no significant difference between the two groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Several factors such as building additional skin incisions, inserting biocritical registration pins, could increase surgery time to a certain extent. The main concern is that the increased operation time may be a potential risk factor for complications 39 . But there is currently no convincing evidence that the robotic group has higher rate of complications, our research also found no significant difference between the two groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Comparing 246 robotic‐assisted UKA and 492 conventional UKA patients from database, Cool et al found the robotic group had a significant lower rate of revision 38 . By analysing the time difference data from the Australian Orthopaedic Association National Joint Arthroplasty Registry, Mart also found the nine months postoperative overall repair rate of the robot system (Mako) was significantly lower than that of the non‐robotically assisted technology (3068 robotically assisted and 6468 non‐robotically assisted UKA procedures) 39 . Comparing the 2%–5.7% of TKA recipients experience failure that necessitate revision surgery within 5 years and 13.3% conventional UKA, robotic UKA is seen as an ideal method to reduce the rate of revision 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…UKA survivorship is considered to be determined by limb alignment [8,10,15,16]. Nevertheless, it still remains controversial in the standard of correct limb alignment following UKA.…”
Section: Discussionmentioning
confidence: 99%
“…Robotically assisted UKA has been introduced, which provides accurate feedback of the relative position of the cutting jigs and the host bones during operation. A number of reports have demonstrated that implantation could be more accurate in robotically assisted UKA as compared with conventional technique on a consistent basis [10][11][12]. Apart from that, robotically assisted operation can be more reproducible, which is of great benefit because the technics of the procedure are challenging in UKA surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation